2023
DOI: 10.1039/d3mh00733b
|View full text |Cite
|
Sign up to set email alerts
|

Quantum tailoring for polarization-discriminating Bi2S3 nanowire photodetectors and their multiplexing optical communication and imaging applications

Abstract: Programmable optoelectronic dichroism has been demonstrated by quantum tailoring of Bi2S3 nanowire photodetectors, and multiplexing optical communications as well as polarimetric imaging have been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Figure 5(d) summarizes the wavelength range and the anisotropic ratio of previously reported polarization sensitive photodetectors built of various nanowire and nanobelt materials. [45][46][47][48][49][50][51][52][53][54][55][56] It is found that the PdBr 2 nanowire photodetector exhibits the optimal anisotropic optoelectronic performance at the near-ultraviolet (405 nm) region. The remarkable polarization-sensitive performance of the PdBr 2 nanowire photodetector holds great promise for designing multifunctional optoelectronic devices and facilitating their integration and miniaturization.…”
Section: Comparisons Of Two Kinds Of Dichroism Ratio Modes (Red Linementioning
confidence: 99%
“…Figure 5(d) summarizes the wavelength range and the anisotropic ratio of previously reported polarization sensitive photodetectors built of various nanowire and nanobelt materials. [45][46][47][48][49][50][51][52][53][54][55][56] It is found that the PdBr 2 nanowire photodetector exhibits the optimal anisotropic optoelectronic performance at the near-ultraviolet (405 nm) region. The remarkable polarization-sensitive performance of the PdBr 2 nanowire photodetector holds great promise for designing multifunctional optoelectronic devices and facilitating their integration and miniaturization.…”
Section: Comparisons Of Two Kinds Of Dichroism Ratio Modes (Red Linementioning
confidence: 99%
“…Selective carrier trapping refers to the spacial localization of a single type of photogenerated carriers (electrons or holes) through unique material/device designs, whilst leaving the other type of photocarriers freely migrating across the photosensitive channel [185]. Since the photoexcited electrons and holes are spacially separated, the lifetime of photocarriers can be markedly extended.…”
Section: Selective Carrier Trappingmentioning
confidence: 99%
“…Metal chalcogenide (MC) semiconductors have garnered unprecedented recognition in the past few decades and have been explored widely in order to complement graphene due to their promising optoelectronic properties. 1–4 These materials, both in nano dimensions and in a thin film geometry, are considered quite exquisite due to their appealing electronic, physical and structural properties. 5,6 In this regard, ternary MCs are of particular interest as they blend the extraordinary properties of MCs with the benefit of physical and chemical property tunability, along with solution processability.…”
Section: Introductionmentioning
confidence: 99%